2008
DOI: 10.1248/bpb.31.847
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Experimental Tumor Metastasis with Age in Senescence-Accelerated Mouse

Abstract: Since most cancer incidence is related to the accumulation of gene mutations, 1) the majority of cancer patients are of the elderly generation and cancer is the highest cause of death for them. These generations are often referred to as "cancer age" and cancer seems to be one of the age-related diseases. 2)On the other hand, cancer development is known to depend on the surrounding host environment.3) For example, tumor cell growth in the young is faster than that in the aged due to alterations in host factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…It has been demonstrated that single SASP factors regulate key processes that facilitate tumor progression and metastasis including proliferation, senescence, angiogenesis, epithelial mesenchymal transition and immune evasion (2,53,55).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that single SASP factors regulate key processes that facilitate tumor progression and metastasis including proliferation, senescence, angiogenesis, epithelial mesenchymal transition and immune evasion (2,53,55).…”
Section: Introductionmentioning
confidence: 99%
“…18,19) Our previous study demonstrated that the aging process caused the enhancement of susceptibility to experimental tumor metastasis in senescence-accelerated mice and the reason why it occurs was suggested to be due to a reduction in immune surveillance potential against metastatic tumor cells with age. 9) These findings suggest that the maintenance of a healthy internal environment in aged animals would improve the age-related weakening of the protective effect against experimental metastasis.…”
Section: Discussionmentioning
confidence: 95%
“…This result confirmed those of our previous study and demonstrated that tumor metastasis was accelerated in an age-dependent manner. 9) In an attempt to inhibit tumor metastasis in old age, we exposed aged SAMP10 mice to GTcatechin water (0.02% Polyphenon70S) for an extended period of time. When the daily intake volume of GT-catechin water was measured, the volume was about 10 ml/d/mouse and was almost the same as for the group given normal water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations